Peran lingkungan keluarga terhadap social media fatigue yang dialami oleh pelajar selama pandemi COVID-19 - Putri, Shafira Angelia (Maliki Interdisciplinary Journal, 2023)
This study discusses the role of the family environment in helping reduce social media fatigue in students during the Covid-19 pandemic. The pandemic has encouraged intensive online learning, potentially causing social media fatigue. Through literature analysis, the study confirmed that family support in the form of motivation and attention can help overcome the negative impact of excessive social media use.